Development of E-Modules for Problem-Based Science Materials in Class IV of SDN Bunulrejo 04 Malang - Mariyati, Dwiki; Wahjoedi, Wahjoedi; Suciptaningsih, Oktaviani Adhi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
This research aims to produce and describe teaching materials in the form of problem-based science e-modules that are valid, practical and effective. This research is a type of research and development with the ADDIE development model, namely Analyze, Design, Development, Implementation, Evaluate. E-Module for problem-based science material which aims to make it easier for students to study independently, as well as helping students solve problems in science material. The research results show that the e-module was designed using the Canva application, containing science material from semester 1 to semester 2, as well as chapters 1 to chapter 8. Apart from that, it also contains learning outcomes, learning videos, room discussions, practice questions and evaluation questions. The e-module developed meets the criteria of being valid, practical and effective. The level of validity of the material from the e-module developed is 90% with the criteria "Very Valid". Meanwhile, the results of the assessment of the level of validity of the e-module media developed were 88.75% with the criteria "Very Valid". The teacher's assessment of the level of practicality of the e-module being developed was 97% in the "Very Practical" category. The results of the e-module effectiveness questionnaire by students or the student response questionnaire showed an e-module effectiveness level of 92.2%. The average Gain Score obtained was 0.65, which was included in the "Quite Effective" category